Copper(II)‐Coordinated α‐Azophenols: Effect of the Metal‐Ion Geometry on Phenoxyl/Phenolate Oxidation Potential and Reactivity. Issue 26 (6th August 2014) - Kochem, Amélie; Carrillo, Alexandre; Philouze, Christian; van Gastel, Maurice; du Moulinet d'Hardemare, Amaury; Thomas, Fabrice
Abstract: Two copper(II) complexes were synthesized from tridentate ligands involving a (Nquinoline, Nazo, Ophenol ) donor set. The copper(II) ion is tetracoordinate with a chloride ion occupying the fourth position of the coordination sphere. Both X‐ray diffraction and electron paramagnetic resonance (EPR) spectroscopy reveal that the copper(II) ion geometry is square planar in1 . In contrast, significant tetrahedral distortions are observed in2, as a result of the steric clash between the hydrogen atoms of the methyl substituent of the quinoline group and the chloride ion. Cyclic voltammetry curves of1 and2 in CH2 Cl2 display a reversible oxidation wave at E 1/2 = 0.59 V and 0.56 V versus ferrocenium/ferrocene, respectively, which was assigned to the phenoxyl/phenolate redox couple. Compounds1 + and2 + were generated and characterized by UV/Vis and EPR spectroscopy. Their reactivity with benzyl alcohol was investigated by kinetic measurements. Abstract : Tetrahedral distortion at the metal ion in a copper(II) complex containing tridentate ligands with a (Nquinoline, Nazo, Ophenol ) donor set is tuned by the α‐quinoline substituent. The Cu II –phenoxyl radical species oxidizes benzyl alcohol at rate constants that are essentially independent of the distortion at the metal center.